Penerapan Project-Based Learning untuk Meningkatkan Kemampuan Menulis Teks Deskripsi Tempat pada Siswa Kelas VI SDN Selagedang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Writing skills are a fundamental component of Indonesian language learning at the elementary school level, yet many students experience difficulties in composing descriptive texts due to limited vocabulary, weak text structure, and low engagement in the learning process. This study aimed to examine the effectiveness of the Project-Based Learning (PjBL) model in improving students’ ability to write descriptive texts about places. The research employed a quantitative approach using a quasi-experimental design with a One Group Pretest–Posttest Design. The subjects of the study were 27 sixth-grade students of SDN Selagedang. Data were collected through descriptive writing tests, observation of learning activities, and documentation. The writing test results were analyzed using descriptive statistics and inferential analysis with a t-test to identify differences in students’ writing ability before and after the implementation of PjBL. The findings revealed a significant improvement in students’ descriptive writing skills following the application of Project-Based Learning, as indicated by higher posttest scores compared to pretest scores. In addition, classroom observations showed increased student engagement, collaboration, and active participation during the learning process. These results suggest that Project-Based Learning provides meaningful learning experiences by integrating observation, collaboration, and authentic writing tasks. The study implies that PjBL can be an effective alternative instructional model for teaching descriptive writing in elementary schools, as it not only enhances students’ writing outcomes but also fosters active and contextual learning environments.